HUBUNGAN ANTARA SELF-ESTEEM DENGAN KECENDERUNGAN BODY DYSMORPHIC DISORDER PADA REMAJA PUTRI DI SMK PGRI 13 CIKUPA TAHUN 2021 - Eka Nur An Nisa; Ayu Pratiwi; Rina Puspita Sari (Nusantara Hasana Berdikari, 2022)
Self-esteem is quite low, it is very easy for teenagers, especially women, to experience indications of Body Dysmorphic Disorder. Because for some teenage girls, physical is the most important aspect in carrying out all their activities, because what guides the perfection of teenagers is the appearance of their body shape. To find out whether there is a relationship between Self-Esteem and the tendency of Body Dysmorphic Disorder in adolescent girls. Methods Used in this study is quantitative descriptive correlation to determine the relationship of Self-Esteem with the tendency of Body Dysmorphic Disorder in Adolescent Girls at SMK PGRI 13 Cikupa. Sampling was done by simple random sampling based on data from SMK PGRI 13 Cikupa in 2021 with a population of 231 so that 146 respondents were obtained. The data analysis technique used is the Chi-Square Test, the results are P-Value 0.000 <0.05, which means ho is rejected and ha is accepted. That there is a relationship between Self-Esteem with the tendency of Body Dysmorphic Disorder in adolescent girls.